ANALYSIS OF POST-PANDEMIC CONSIGNMENT SALES SYSTEMS AND PROCEDURES IN MSMEs SNACK CV. AURA SUFA MALANG REGENCY - Evi Suwarni; Masitha Nisa Akmalia; Tatiana Kristianingsih; Ika Kusumasasti (Jurnal Ekonomi, 2023)
The impact of the Covid 19 pandemic that has hit the world, causing more and more people to be infected with Covid 19. Therefore, the Government of Indonesia has implemented social restrictions to minimize the spread of the virus. These social restrictions make people's activities limited and unusual, making all community activities hampered. Economic activities are no exception. The large risk of bankruptcy in Micro, Small and Medium Enterprises (MSMEs), makes a lot of Micro, Small and Medium Enterprises (MSMEs) go out of business, so millions of people lose their jobs. Given the importance of the role of MSMEs in Indonesia, there is a need for a strategy to encourage the revival of MSMEs in Indonesia. Increasing sales is one way to revive the economy from MSMEs which are currently sluggish. One strategy that can be run is to make consignment sales. This research will be conducted on MSMEs because MSMEs are the weakest sector affected by Covid-19, especially those engaged in snacks. Based on a preliminary survey of CV. Aura Sufa in Malang Regency, which is engaged in selling fruit chip snacks, is known that the Covid-19 pandemic has had a major impact on her finances and there has been a significant decrease in revenue from sales proceeds and non-smooth payments from the consignee who is a business partner. The study used qualitative methods with in-depth interviews of company owners and employees. From the analysis of the research results, it was concluded that there was an evaluation of the consignment sales system such as improving flows and procedures that were previously manual to become systemized, sales and marketing systems that use social media, developing partnership system models and completeness of documents related to consignment sales administration. So that with the flow of systems and administrative procedures for consignment sales, it can have an impact on increasing sales volume and smooth administration of accounts receivable collection.